Graphene‐Based Sorbents for Multipollutants Removal in Water: A Review of Recent Progress. (1st December 2020) - Yap, Pei Lay; Nine, Md Julker; Hassan, Kamrul; Tung, Tran Thanh; Tran, Diana N. H.; Losic, Dusan
Abstract: The coexistence of multiple toxic water pollutants (heavy metals, organic dyes, oils, and organic solvents) limits the sustainable supply of clean water worldwide and urges the development of advanced water purification technology that can remove these contaminants simultaneously. Since its discovery, graphene‐based materials have gained substantial attention toward development of new‐generation sorbents for water purification. Despite several recently published reviews on water purification technology using graphene and its derivatives, there is still a gap in the review considering multiple water‐pollutant remediation using advanced graphene materials. In this review, in the first instance, a comparative structure–function–performance relationship between graphene‐based sorbents and the multipollutants in water is established. A fundamental correlation is made between the sorption performance for diverse pollutants in water with the more specific adsorption properties (surface area, pore size, type of functional groups, C/O, C/N, and C/S atomic ratio) of advanced graphene sorbents. Second, the underlying interaction mechanisms are uncovered between different classes of water pollutants using single graphene‐based sorbents. Third, the rational design of advanced multipollutant sorbents based on graphene is elaborated. The reality, challenges, and opportunities of advanced graphene materials as emerging sorbents for sustainable water purification technology are finally presented in the last section. Abstract : Herein, the recent development of graphene‐based sorbents for the uptake of multipollutants are reviewed to establish a structure‐function‐performance relationship based on graphene doping and its functionalization. A link is made between the adsorption properties with the sorption performance of advanced graphene sorbents with multipollutants. The reality, challenges, and opportunities for advanced graphene materials as sustainable water purification technology are highlighted.